Job Demands, Job Resources And Work-Life Balance Among The Academicians In The Private Universities In Egypt: The Moderating Role Of Self-Efficacy - Selim, Ingy Mohamed Sameh Mohamed Abdelaal (2024)
Work-life balance is essential for all individuals; it increases job satisfaction and life satisfaction and reduces stress, leading to internal happiness and contentment. However, work-life balance is a significant problem among academicians working in Egypt's top 10 private universities. Thus, recognising the factors that affect the academicians' work-life balance is essential. Firstly, this study developed an integrative model using the Job Demands and Resources (JD-R) Theory and the Conservation of Resources (COR) Theory to test the effect of job demands: workload, mental demands, and emotional demands on work-life balance. Secondly, it investigates the effect of job resources: supervisor support, co-worker support, and decision authority on work-life balance. This study also recognises the importance of personal resources among academicians; hence, it examines the moderating effect of self-efficacy on the relationship between job demands, job resources, and work-life balance. Data were collected from 504 academicians employed in the top 10 private universities in Egypt. SPSS and Partial Least Square-Structure Equation Modeling (PLS-SEM) were used for data analysis. The findings showed that workload, mental and emotional demands significantly and negatively affected work-life balance. Moreover, co-worker support and decision authority had a significant and positive effect on work-life balance.